THE SYSTEM OF INSTITUTIONS ADJUDICATING ADMINISTRATIVE SANCTIONS - Markevičiūtė, Milda (Teisė, 2015)
In this article the enforced regulation regarding institutions which are enabled to impose administrative liability is being analysed. It is also being compared with the regulation proposed by the Draft Code of Administrative Offences regarding institutions which are enabled to adjudicate cases of administrative offenses. While comparing the enacted regulation with the proposed one, advantages and debatable aspects of the discussed system are identified. The rule that institutions, which officials examined the offences, are to be the ones that adjudicates the case is also analysed in this article. The impartiality and legal education of the officials are being questioned, as well as the correspondence of the discussed rule with Article 109 of the Constitution and the question whether public administrative bodies have authority to impose administrative liability. After careful evaluation of these issues, it is to be concluded that the legal safeguards are appropriate and effective enough in order to ensure impartial and fair adjudication of the case. The proposed regulation regarding chiefs of administrative units and the conditions under which the certain case is to be adjudicated in courts is being analysed. All in all, it is concluded that the proposed regulation in respect of institutions which shall adjudicate the cases has more advantages than presently effective regulation.